The Effect Of Competency And Career Development On Employee Performance With Employee Engagement As An Intervening Variable At Bank Papua, Main Branch Office, Jayapura - Aryani , Ari Meirika; Daga , Rosnaini; Rosanti, Novita (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to examine the influence of competence and career development on employee performance with employee engagement as an intervening variable at Bank Papua Main Branch Jayapura. The research was conducted at Bank Papua Main Branch Jayapura over a period of two months, from June to July 2025. The population and sample in this study consisted of 84 employees of Bank Papua Main Branch Jayapura. This research used a survey method by distributing questionnaires to the research subjects. The statistical method used to test the hypotheses was Partial Least Squares (PLS) with the help of an application. The analysis results show that competence has a positive and significant effect on employee engagement; career development has a positive and significant effect on employee engagement; competence has a positive and significant effect on employee performance; career development has a positive but not significant effect on employee performance; employee engagement has a positive and significant effect on employee performance; competence has a positive and significant effect on employee performance through employee engagement as an intervening variable; and career development has a positive and significant effect on employee performance through employee engagement as an intervening variable